Genomic sequencing and in vivo footprinting of an expression-specific DNase I-hypersensitive site of avian vitellogenin II promoter reveal a demethylation of a mCpG and a change in specific interactions of proteins with DNA. - Saluz, H P (1988)
Genomic sequencing was used to study the in vivo methylation pattern of two CpG sites in the promoter region of the avian vitellogenin gene. The CpG at position +10 was fully methylated in DNA isolated from tissues that do not express the gene but was unmethylated in the liver of mature hens and estradiol-treated roosters. In the latter tissue, this site became demethylated and DNase I hypersensitive after estradiol treatment. A second CpG (position -52) was unmethylated in all tissues examined. In vivo genomic footprinting with dimethyl sulfate revealed different patterns of DNA protection in silent and expressed genes. In rooster liver cells, at least 10 base pairs of DNA, including the methylated CpG, were protected by protein(s). Gel-shift assays indicated that a protein factor, present in rooster liver nuclear extract, bound at this site only when it was methylated. In hen liver cells, the same unmethylated CpG lies within a protected region of approximately equal to 20 base pairs. In vitro DNase I protection and gel-shift assays indicate that this sequence is bound by a protein, which binds both double- and single-stranded DNA. For the latter substrate, this factor was shown to bind solely the noncoding (i.e., mRNA-like) strand.